Hillslopes development in Selangor: a case study of the law and regulations / Nur Fathiah Marzuki, Ahmad Soffian Mohd Shariff and Tuan Ruzuaini Tuan Lah - Marzuki, Nur Fathiah; Mohd Shariff, Ahmad Soffian; Tuan Lah, Tuan Ruzuaini (2008)
Hillslopes development in Selangor has ever been a controversial subject since. the transition of the new government. The banning of hillslopes development by the state government was accepted with mixed emotion by the community. This research is to find out how does hillslopes development affects the community in the light of public security, environmental issues and the law regarding hill-slopes development in the State of Selangor. The development on hills had been conceived on short-term benefits with the rights of the individual prevailing. However, there are rising community expectations concerning the maintenance of visual values, natural habitat and biodiversity around urban and growth centers. Hill slopes are prone to environmental hazards such as soil erosion and landslide as is evident from past incidences, resulting in loss of lives and property. Development in these areas can compound such hazards and render them highly visible and costly to deal with. We understand that there is much at stakes when hillslopes development is done without proper supervision. We hope that our research can give new insight of this topic and come out with a better solution. The researchers are done with reference of books, newspaper articles, internet postings and interviewing the parties that involve in hillslopes development.